(untitled) (International Journal of Environmental Sciences, 2025)
Using an analytical and critical approach, this study explores the economic and environmental damages eligible for compensation under the civil liability regime in the nuclear field. It examines the concepts, types, and methods for assessing such damages. The study finds that nuclear environmental damage includes any harm originating from a nuclear facility that affects the environment or any of its components due to the hazardous properties of nuclear fuel, radioactive materials, or waste. The competent court adjudicating nuclear-related economic or environmental damage has discretionary authority to assess compensation in accordance with provisions set forth in nuclear-specific laws and relevant international agreements. The study recommends expanding the scope of compensation for nuclear damage without imposing restrictive limitations, allowing the assessment of compensation to be based on scientific, medical, and evidentiary findings. This ensures that affected individuals are not denied their rightful compensation due to narrow interpretations of nuclear harm.